GENETIC AND POST-GENETIC MOLECULAR AND ISOTOPIC FRACTIONATIONS IN NATURAL GASES - Prinzhofer A.A.; Huc A.Y. (My University, 1995)
From molecular and isotopic data obtained with a new separation technique, and from published data, it is possible to discuss the relative importance of genetic and post-genetic molecular and isotopic fractionations affecting natural gases. Using a δ13Ci-δ13Cj versus ln() plot, we suggest from the ethane-propane system that it is possible to distinguish hydrocarbon gases generated by the primary cracking of kerogen, from gases generated by the secondary cracking of oil. With the methane-ethane system, we discuss mixing of thermogenic and biogenic gases, degree of maturity of thermogenic gases, and residues of diffusive leakage. We consider that although the prime order of fractionation in gases is due to genetic phenomena, second-order effects due to post-genetic fractionation (diffusion, oxidation etc.) may be recognized, and in some cases must be taken into account to model the geochemical data on a gas field.